Effect of Covid-19 Pandemic on Recreational Awareness and Quality of Life - Mehmet Demirel; Alper Kaya; Davut Budak; Mustafa Sabır Bozoğlu; Yusuf Er (Türk Spor ve Egzersiz Dergisi)
The Covid-19 pandemic has significantly changed individuals’ quality of life. Authorities have taken various measures to protect general public health. These measures, which are taken to fight the virus effectively during the pandemic, have also limited many recreational activities that individuals can do in daily life. A total of 818 people participated in this study, in which the recreational awareness levels of university students and the effects of the Covid-19 pandemic on quality of life were discussed in terms of various variables. The SPSS package program was used in the analysis of the research data, and Kolmogorov Smirnov test and Shapiro tests were applied to determine the normality of the data distribution. Since the data did not have a normal distribution, that is, non-parametric distribution, besides descriptive statistical models, Mann Whitney U, Kruskal Wallis test, and correlation analysis were applied. A significant positive relationship was found between recreational awareness and the effect of the Covid-19 pandemic on quality of life. As a result, a significant difference was found between the recreational awareness levels of university students and their demographic variables only in the variable of being infected with the Covid-19, and no significant difference was found in other variables. Significant differences were found between the effect of the Covid-19 pandemic on quality of life and age, gender, level of welfare, and the Covid-19 infection.